Peran Guru Bahasa Indonesia Dalam Membangun Karakter Siswa Yang Berlandaskan Nilai Kristiani di Era Digital di SMA Swasta Parulian 1 Medan - Claudia Ratna Ningsih; Eylen Yossi Siagian; Ezra Natasya Hutabarat; Putri Octavia Simbolon; Nanda Claudia Pardede (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This research aims to analyze the role of Indonesian language teachers in building students' character based on Christian values ​​in the digital era, how teachers try to maintain a balance between the use of technology and instilling moral values, the challenges faced in this process, and the strategies applied in language learning Indonesia at SMA Swasta Parulian 1 Medan. This research uses a qualitative descriptive method, which aims to describe and understand phenomena in depth through data collection from interviews and documentation. Research data was collected through direct interviews with Indonesian language teachers and students at SMA Swasta Parulian 1 Medan. The research results show that teachers strive to maintain a balance between the use of technology and the cultivation of moral values ​​through an effective approach and collaboration with other parties. The main challenge faced is the negative influence of digital media on students' character, but this can be overcome with consistent moral guidance. The role of Indonesian language teachers in shaping students' character in the digital era is very important, and consistent moral guidance is able to overcome the challenges posed by the development of digital technology.